Brief psychological intervention after self-harm: randomised controlled trial from Pakistan. (June 2014) - Husain, Nusrat; Afsar, Salahuddin; Ara, Jamal; Fayyaz, Hina; Rahman, Raza ur; Tomenson, Barbara; Hamirani, Munir; Chaudhry, Nasim; Fatima, Batool; Husain, Meher; Naeem, Farooq; Chaudhry, Imran B.
Abstract : Background: Self-harm is a major risk factor for completed suicide. Aims: To determine the efficacy of a brief psychological intervention – culturally adapted manual-assisted problem-solving training (C-MAP) – delivered following an episode of self-harm compared with treatment as usual (TAU). Method: The study was a randomised controlled assessor-masked clinical trial (trial registration: ClinicalTrials.gov NCT01308151). All patients admitted after an episode of self-harm during the previous 7 days to the participating medical units of three university hospitals in Karachi, Pakistan, were included in the study. A total of 250 patients were screened and 221 were randomly allocated to C-MAP plus treatment as usual (TAU) or to TAU alone. All patients were assessed at baseline, at 3 months (end of intervention) and at 6 months after baseline. The primary outcome measure was reduction in suicidal ideation at 3 months. The secondary outcome measures included hopelessness, depression, coping resources and healthcare utilisation. Results: A total of 108 patients were randomised to the C-MAP group and 113 to the TAU group. Patients in the C-MAP group showed statistically significant improvement on the Beck Scale for Suicide Ideation and Beck Hopelessness Inventory, which was sustained at 3 months after the completion of C-MAP. There was also a significant reduction in symptoms of depression compared with patients receiving TAU. Conclusions: The positive outcomes of this brief psychological intervention in patients attempting self-harm are promising and suggest that C-MAP may have a role in suicide prevention.